Proses Justifikasi Matematis Siswa Melalui Accelerated Learning Berdasarkan Kemampuan Awal Matematis - Supriani, Yani; Oktaviyanthi, Rina (PT. LANCAR MEDIA KOMUNIKASI, 2024)
In this research, justification ability is viewed from four indicators, namely the ability to develop mathematical arguments (proving), the ability to analyze (basic level), the ability to generalize, the ability to make decisions which are first analyzed for their initial mathematical abilities which are divided into three categories, namely high, medium and low levels. . The method used is quantitative with a quasi-experimental design, with division into experimental classes and control classes. The results obtained from each sample based on the initial mathematical ability level category are the highest N-Gain sequence at high KAM (0.3943), followed by medium KAM (0.3600) and overall KAM (0.514) and finally low KAM (0 ,22470).